Pengaruh Tekanan Waktu, Materialitas, Risiko Audit Dan Tindakan Supervisi Terhadap Penghentian Prematur Atas Prosedur Audit (Studi Empiris Pada Auditor Di Badan Pengawas Keuangan Dan Pembangunan Daerah Istimewa Yogyakarta) - Syafrina Sholehati, Nadia, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
Premature sign off of audit procedure is one form of reduced audit quality. This act refers to falsely signed off a require audit step, which is not covered by other step, without completing the work or nothing the omission of the procedure butauditor dare to express opinion based on that procedure. This research was purposes intended to identify the impact of time pressure, materiality,audit risk and supervision on the premature sign off of the audit procedure at the Development Finance Comptroller (BPKP) in DIY This research is qualitative research. The sample in thia research is 60 auditors employed at the BPKP in DIY, was taken using the sampling purposive technique. The data that used were primary data by survey method in which questionnaire was distributed to the respondents. The data were examined using the tests of validity and reliability, classical assumption, normality, multicolinearity, and heteroscedastisity. The hypothesis was analyzed using the Multiple Regression Analysis assisted with SPSS 19.0 for Windows program. The result of the study showed that the time pressure, materiality,audit risk,and supervision significant effect to the premature sign off of the audit procedur.